The Potential of Sustainable Palm Oil Downstream to Improve the Green Economy of the Community - Julia Julia; Darman Saputra; Hamsani Hamsani; Dian Prihardini Wibawa (Journal of Multidisciplinary Academic Business Studies, 2026)
Purpose: This study analyzes the transformation of the green economy in the downstream oil palm industry in Bangka Belitung Islands Province, focusing on how downstreaming, technological innovation, and government policies can accelerate the shift from a resource-based economy to a high-value, low-carbon economy. Research Methodology: A mixed-methods design was used, with quantitative panel data from 2014–2024 (33 observations from three districts) analyzed using the Fixed Effect Model (FEM). Qualitative data was gathered through in-depth interviews with 35 stakeholders from industry, government, and farming sectors. Results: The study finds that palm oil down streaming, technological innovation, and government policies positively and significantly strengthen the green economy. The green economy plays a mediating role in transitioning to the "New Economy." Synergy between public policies and technological innovation improves energy efficiency by 20%, reduces carbon emissions, and boosts farmers' incomes by 15-20%. Conclusions: The research concludes that Instagram content visibility is influenced by platform affordances and curatorial power, reflecting actor positions and engagement strategies. Destination marketing strategies should integrate culture and sustainable tourism through narrative-driven representations. Limitations: The study is limited to three districts in the Bangka Belitung Islands, which may affect generalization to other regions. The panel data population (33 observations) is also limited due to the focus on specific time periods and regions. Contribution: This study extends the Green Structural Transformation framework and provides a policy framework for developing an inclusive green industry roadmap and enhancing export competitiveness.